PENGARUH RASIO CAMEL TERHADAP KINERJA KEUANGAN PERBANKAN SYARIAH - Indyarwati, Emmy Vismia; Handayani, Nur (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is aimed to find out the influence of CAMEL ratio to the financial performance of sharia banking. This research is used CAMEL ratio i.e. Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Net Profit Margin (NPM), operational cost, and operational revenue (BOPO), Finance to Deposit Ratio (FDR) to the financial performance which is measured by using Return On Asset (ROA). The research sample consist of 6 companies of sharia banking which have been selected by using purposive sampling. The research population is sharia bankings which are listed in Indonesia Stock Exchange in 2013-2015 periods. The statistic test instrument is SPSS 20 which has been carried out by using classic assumption test and multiple linear regressions analysis. The result of the research shows that Capital Adequacy Ratio (CAR), Non Performing Financing (NPF), Operational cost and operational revenue (BOPO), Finance to Deposit Ratio (FDR) have significant and negative to the Return on Asset (ROA). Meanwhile, Net Profit Margin (NPM) has significant and positive influence to the Return on Asset (ROA).Keywords: Capital, Asset, Management, Earning, Liquidity.